ORAL CORRECTIVE FEEDBACK IN CHILDREN INTERACTION IN IMMERSION CLASS - Kalisa, Pasca (Language Circle: Journal of Language and Literature, 2017)
The present study investigates the occurrence of corrective feedback in the learning process and teachersâ perspectives in giving the corrective feedback. The participants in the present study were two teachers and twelve children ranging from five to six years old. They were enrolled in Mondial School, an immersion school in Semarang, Indonesia. All of the children were Indonesians and some of which were Chinese descendants. Â This study applied a descriptive qualitative approach in the purpose of analyzing each utterance produced by teachers in classroom interaction and teachersâ perspectives towards the corrective feedback used. As the basis of data analysis, Ranta&Lysterâs Classification of corrective feedback was applied. The findings showed that 85% of teachersâ utterances used didactic recasts in giving feedback to childrenâs errors. These errors were mostly grammatical errors due to language transfer. Based on the findings, it can be concluded that the teachers have a tendency to use corrective feedback expressed explicitly in correcting speech errors in children, rather than implicitly or indirectly. Meanwhile, the perception of teachersâ tendency in giving corrective feedback through didactic recast was due to the effectiveness of didactic recast in encouraging children to correct errors in their speech. Teachers also added that giving corrective feedback was intended to encourage children to be aware of the structure of the language more precise without teaching grammar deductively, so the grammar was expected to be absorbed and understood by the children themselves.